The association between perceived social support and self-management behaviors in adolescents and young adults with inflammatory bowel disease: the chain mediating role of basic psychological needs and anxiety/depression - Yangfan Zhu; Yangfan Zhu; Yueyue Chen; Yuman Tang; Xin Zhang; Qiao Shen; Fei Li; Hao Wang; Xianlan Zheng (Frontiers in Psychology)
IntroductionThe incidence of inflammatory bowel disease (IBD) has been increasing, with adolescents and young adults being the peak age of onset. Self-management behaviors were demonstrated to enhance remission and quality of life, yet the mechanisms influencing self-management behaviors remained under-explored. Perceived social support is crucial to self-management behaviors, alongside the roles of basic psychological needs, anxiety, and depression.MethodsWe conducted a two-center cross-sectional survey in China from July to August 2024 via convenience and snowball sampling to investigate how these variables influence self-management behaviors. Data were collected utilizing the structured self-report questionnaires. Mediating effects were analyzed using the bootstrap method.ResultsA total of 183 adolescents and young adults with IBD (male: 71.58%), aged 13 to 24 years old (M = 20.33, SD = 3.03), were included in the analysis. The research findings include the following points: (1) perceived social support positively predicted self-management behaviors (β = 0.767, P < 0.001); (2) perceived social support affected self-management behaviors through chain mediation involving basic psychological needs and anxiety/depression.ConclusionClinical practitioners should enhance social support for adolescents and young adults with IBD and improve their perceptions of such support, fulfill basic psychological needs, and alleviate anxiety and depression to promote effective self-management behaviors.